The Implementation of Ant Colony Algorithm In Finding The Shortest Travel Route of Palembang Tourism By Android Based. (February 2019) - Faizah, Safira; Novianti, Leni; Kom., S.; Kom., M.; Novita, Nita; E., S.; M, M.
Abstract: Ant Colony is a methodology produced by observing ants. In this algorithm, ants as agents assigned to find solutions to an optimization problem, like to find the optimal solution on Traveling Salesman Problem (TSP). Therefore, the research will apply ant colony algorithm to search the shortest path of tourism in Palembang City, covering tourist destinations, culinary, hotels and handicrafts. The results of this study, will provide ease of tourists in accessing tourist destination information and information about travel routes easily via mobile applications with android operating system and use of Google Maps API.